Análise morfoestrutural, mineralógica e litogeoquímica das ocorrências de kimberlitos da região de dom expedito lopes - província kimberlítica de Picos, Piauí - Rosa, Gabriela Meireles (2020)
Kimberlites are volcanic rocks of deep origin in the mantle, which usually manifest themselves in the craton zones and tend to occur in clusters or provinces. Both in Brazil and in other parts of the world, they are extremely altered, with a great mineralogical and textural variety. In the state of Piauí, 51 Kimberlitic bodies were discovered, which are grouped into seven distinct groups and make up the Gilbués and Picos Provinces. This thesis aims: to morphostructurally correlate the Kimberlitic provinces of Picos and Gilbués through remote sensing and based on the existing superficial morphological aspects; petrographically analyze samples obtained from the Picos kimberlitic bodies; perform mineralogical analysis using Scanning Electron Microscope (MEV) and dispersive energy spectroscopy (EDS); and to analyze kimberlite samples from the lithogeochemical point of view using the ICP-MS plasma emission spectrometry. The morphostructural correlation between the two provinces of the state indicates a strong drainage pattern in both, with a positive relief shape in the Picos and lineaments with a regional NE-NW trend. It is admitted that the kimberlites are housed in sedimentary rocks of the Parnaíba Basin; and temporarily those in Picos are younger than those in Gilbués.The conditions of the outcropping rocks in the geological mapping carried out indicated a greater or lesser degree of alteration, which led to the concentration of collections in more preserved outcrops in the municipality of Dom Expedito Lopes. Petrographically, Dom Expedito Lopes' kimberlites exhibit mineralogical variation with the presence of minerals, such as: garnet, perovskite, cr-spinel, olivine, serpentine, clinopyroxene, enstatite, apatite, and ilmenite. The mineralochemical analyzes by MEV-EDS corroborate with petrography and bring better characterization in the identification of kimberlites and definition of the main constituent elements of the minerals. It can be said that the kimberlites of the Picos region are in need of more detailed investigation, considering that research on this subject is almost always confidential, held by mining rights holders. This area is not explored, unlike the Kimberlitic Province of Gilbués, which has been mined for more than 70 years, however, according to current DNPM data, it is required by a foreign diamond company. However, it is controversial whether these bodies are truly fertile.However, it is important to attribute the prevailing intrusions in the Kimberlitic Province of Picos to the Crater facies, due to the high content of Si coming from the embedding rocks, indicating crustal contamination.